Smart handover for hybrid LiFi and WiFi networks - Wu, X; O’Brien, D; Deng, X; Linnartz, J-PMG (IEEE, 2020)
This work investigates handover in hybrid light fidelity (LiFi) and wireless fidelity (WiFi) networks (HLWNets). In such a network, the handover process becomes challenging due to two main factors: i) the relatively short coverage range of a single access point (AP), and ii) the largely overlapping coverage areas of different networks. As a result, HLWNets are susceptible to frequent handovers. To reduce the handover rate, the concept of handover skipping (HS) was introduced, which enables handovers between non-adjacent APs. However, conventional HS methods rely on knowledge about the user’s trajectory, which is not readily available at the AP. In this paper, a novel HS scheme is proposed on the basis of reference signal received power (RSRP) and its rate of change, with an adaptive network preference adopted. Since RSRP is commonly used in the existing handover schemes, the proposed method requires no additional signalling between the user and the AP. Simulation results show that the new method can effectively reduce unnecessary handovers, especially those between LiFi and WiFi. Compared to the standard and trajectory-based handover schemes, the proposed method improves network throughput by up to about 120% and 30%, respectively.